Endrew F. v. Douglas County School District (2017): Implications for Educating Students With Emotional and Behavioral Disorders. (November 2019) - Yell, Mitchell L.
In 2017, the Supreme Court ruled on a special education case Endrew F. v. Douglas County School District . In this important case, the High Court addressed the degree of educational benefit necessary for a school district to fulfill the requirements for a free appropriate public education (FAPE) under the Individuals With Disabilities Education Act (IDEA). The ruling was especially meaningful for the field of emotional and behavioral disorders, because the plaintiff in this case, Endrew F., exhibited serious academic difficulties and behavior problems. In this article, I first analyze the IDEA's definition of FAPE and the importance of addressing students' behavior problems in their individualized education programs (IEPs) to provide a FAPE. Second, I examine the U.S. Supreme Court's ruling in the Endrew decision, specifically addressing the impact of the school district's failure to address a student's behaviors in his IEP. Third, I discuss the implications of the Endrew ruling for developing and implementing IEPs for students with serious behavior problems. I end by advocating for changes in the upcoming reauthorization of the IDEA to bring the law into conformity with the spirit and letter of this important ruling.